Interventions to improve patient understanding of cancer clinical trial participation: a systematic review. (20th January 2016) - Kao, C.Y.; Aranda, S.; Krishnasamy, M.; Hamilton, B.
Abstract : Patient misunderstanding of cancer clinical trial participation is identified as a critical issue and researchers have developed and tested a variety of interventions to improve patient understanding. This systematic review identified nine papers published between 2000 and 2013, to evaluate the effects of interventions to improve patient understanding of cancer clinical trial participation. Types of interventions included audio‐visual information, revised written information and a communication training workshop. Interventions were conducted alone or in combination with other forms of information provision. The nine papers, all with methodological limitations, reported mixed effects on a small range of outcomes regarding improved patient understanding of cancer clinical trial participation. The methodological limitations included: (1) the intervention development process was poorly described; (2) only a small element of the communication process was addressed; (3) studies lacked evidence regarding what information is essential and critical to enable informed consent; (4) studies lacked reliable and valid outcome measures to show that patients are sufficiently informed to provide consent; and (5) the intervention development process lacked a theoretical framework. Future research needs to consider these factors when developing interventions to improve communication and patient understanding during the informed consent process.